2021
DOI: 10.1111/ijfs.15406
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites of the Soy Sauce Koji Making with Aspergillus niger and Aspergillus oryzae

Abstract: Koji making comprises multi-microbial interactions and is an important part of soy sauce production. The aim of this study was to determine interactions and investigate metabolites in koji by ultraperformance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q/ TOF-MS). Differential metabolites between groups of single strain (Aspergillus oryzae) and mixed strains (Aspergillus niger and A. oryzae) koji making were screened and identified using an untargeted metabolomics appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This indicated that α ‐glucosidase and phospholipase C maintained their enzymatic reaction roles in both the koji‐making stage and the moromi fermentation stage. α ‐Glucosidase and phospholipase C could be observed as early as in the koji‐making stage, and in this study they were upregulated throughout the moromi fermentation stage 46,52 . After α ‐amylase had hydrolyzed starch, α ‐glucosidase could continue to further hydrolyze the products 46 .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This indicated that α ‐glucosidase and phospholipase C maintained their enzymatic reaction roles in both the koji‐making stage and the moromi fermentation stage. α ‐Glucosidase and phospholipase C could be observed as early as in the koji‐making stage, and in this study they were upregulated throughout the moromi fermentation stage 46,52 . After α ‐amylase had hydrolyzed starch, α ‐glucosidase could continue to further hydrolyze the products 46 .…”
Section: Resultssupporting
confidence: 53%
“…⊍-Glucosidase and phospholipase C could be observed as early as in the koji-making stage, and in this study they were upregulated throughout the moromi fermentation stage. 46,52 After ⊍-amylase had hydrolyzed starch, ⊍-glucosidase could continue to further hydrolyze the products. 46 In addition to its function of hydrolyzing lipid, phospholipase C was also present in the signaling pathway essential for umami taste transduction.…”
Section: Mechanism Of Critical Enzymatic Systems In Soy Sauce Mashmentioning
confidence: 99%
“…Aspergillus oryzae, the mold used in yellow rice wine production, produces a range of compounds through metabolism, including esters, fatty acids, and alcohols. These substances significantly influence the taste, aroma, and overall flavor profile of the beverage and contribute to the unique flavor and aroma of yellow rice wine [49]. The Meyerozyma genus strain YB-12, isolated from the fermentation materials of yellow rice wine, possesses a similar ability to produce ethanol as the brewing yeast NRRL Y-567.…”
Section: Microbial Improvement Of the Composition And Quality Of Yell...mentioning
confidence: 99%
“…All the references indicated the fermentation environment and production scale can make significant differences in the mature koji. Most of the studies about highly efficient strains were researched in laboratory conditions (Ao et al, 2018 ; Ding et al, 2019 ; Yee et al, 2021 ; Hu et al, 2022 ), and their performance in the actual production environment of the factory remains unclear.…”
Section: Introductionmentioning
confidence: 99%